The two faces of an employee: exploring the relationships between organizational citizenship behaviour, counterproductive work behaviour and job satisfaction - Kanafa-Chmielewska, Dorota (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2019)
Overlapping items and agreement response options were perceived as a measurement artefact that may have caused classical, yet hypothetically biased, findings on the subject. The participants were Central European employees (n = 655). The results did not support positive correlations between organizational citizenship behaviour (OCB) and counterproductive work behaviour (CWB) and the negative relations between the two and job satisfaction. They were consistent with previous and intuitive findings that demonstrated the negative relation between citizenship and counterproductive work behaviour, as well as with reverse interrelations of the two types of organizational behaviour with job satisfaction. Confirmatory factor analysis was conducted to explore OCB and CWB dependency on job satisfaction. That findings show the two-face nature of employees. Explanations of intuitive and counterintuitive findings in the subject are discussed
Argumenta Oeconomica, 2019, Nr 1 (42), s. 317-336
Keywords: organizational citizenship behavior; counterproductive work behaviours; job satisfaction